ELASTISITAS SUKU BUNGA TERHADAP PENYALURAN KREDIT INVESTASI PERSEKTOR EKONOMI DI KALIMANTAN BARAT - B01108053, FITRIYANI (Jurnal Pembangunan dan Pemerataan, 2013)
The title of the study is "Elasticity Of Interest Investment Loan Disbursement Economic Per sector in West Kalimantan". This study aims to examine and analyze the effect of interest rates on investment loans per sector Economics in West Kalimantan and to determine the level of the interest rate elasticity of investment lending per sector economies in West Kalimantan. This study used time series data between 2007 first quarter to 2011 fourth quarter, which is a secondary data from Bank Indonesia at Banking Statistics of Indonesia. The research method using Simple Linear Regression and elasticity test. Based on the estimates, the study found that the economic sector in West Kalimantan are significant in the mining, industrial, Electricity, Gas, Water, Building, commerce, transport, services and others. While the agriculture sector is not significantly affected. Then the sectors of the economy in western Borneo is Elastic contained in the mining, industrial, Electricity, Gas, Water, Building, commerce, transport, services and others. As well as the agricultural sector is Inelastic. Keywords: Interest Rates, Economic Persector Distribution of Investment Credit in West Kalimantan.